Maternal polymorphisms in glutathione-related genes are associated with maternal mercury concentrations and early child neurodevelopment in a population with a fish-rich diet. (June 2018) - Wahlberg, Karin; Love, Tanzy M.; Pineda, Daniela; Engström, Karin; Watson, Gene E.; Thurston, Sally W.; Yeates, Alison J.; Mulhern, Maria S.; McSorley, Emeir M.; Strain, J.J.; Smith, Tristram H.; Davidson, Philip W.; et al.
Abstract: Introduction: Glutathione (GSH) pathways play a key role the metabolism and elimination of the neurotoxicant methylmercury (MeHg). We hypothesized that maternal genetic variation linked to GSH pathways could influence MeHg concentrations in pregnant mothers and children and thereby also affect early life development. Methods: The GCLM (rs41303970, C/T), GCLC (rs761142, T/G) and GSTP1 (rs1695, A/G) polymorphisms were genotyped in 1449 mothers in a prospective study of the Seychellois population with a diet rich in fish. Genotypes were analyzed in association with maternal hair and blood Hg, fetal blood Hg (cord blood Hg), as well as children's mental (MDI) and motor development (PDI; MDI and PDI assessed by Bayley Scales of Infant Development at 20 months). We also examined whether genotypes modified the association between Hg exposure and developmental outcomes. Results: GCLC rs761142 TT homozygotes showed statistically higher mean maternal hair Hg (4.12 ppm) than G carriers (AG 3.73 and GG 3.52 ppm) ( p  = 0.037). For the combination of GCLC rs761142 and GCLM rs41303970, double homozygotes TT + CC showed higher hair Hg (4.40 ppm) than G + T carriers (3.44 ppm; p  = 0.018). No associations were observed between GSTP1 rs1695 and maternal hair Hg or between any genotypes and maternal blood Hg or cord blood Hg. The maternal GSTP1 rs1695 rare allele (G) was associated with a lower MDI among children (β = −1.48, p  = 0.048). We also observed some interactions: increasing Hg in maternal and cord blood was associated with lower PDI among GCLC rs761142 TT carriers; and increasing Hg in hair was associated with lower MDI among GSTP1 rs1695 GG carriers. Conclusions: Maternal genetic variation in genes involved in GSH synthesis is statistically associated with Hg concentrations in maternal hair, but not in maternal or fetal blood. We observed interactions that suggest maternal GSH genetics may modify associations between MeHg exposure and neurodevelopmental outcomes. Highlights: Glutathione (GSH) is important for metabolism of the neurotoxicant methylmercury (MeHg). Maternal GSH synthesis-related genotypes were associated with Hg in maternal hair. Interactions were found between genotypes and Hg on children's neurodevelopment. Maternal GSH genetics may influence fetal sensitivity to MeHg exposure.